(untitled) (CIPEEX, 2025)
Chronic nasal obstruction in childhood, often caused by adenoid hypertrophy, is a prevalent and multifactorial condition with potential clinical, cognitive, and psychosocial repercussions. This functional alteration compromises the respiratory pattern and is associated with mouth breathing, sleep disturbances, craniofacial changes, and poor school performance. Despite its high incidence in the pediatric population, the literature still presents gaps regarding the systematization of these impacts and the ideal timing for clinical or surgical intervention. This study conducted an integrative literature review guided by the PICO strategy to investigate the effects of chronic nasal obstruction—especially due to adenoidal hypertrophy—on child development, with a specific focus on sleep quality and functional and cognitive consequences. The search was carried out in the SciELO, PubMed, and LILACS databases, using the descriptors “Adenoids,” “Nasal obstruction,” “Sleep,” and “Child development,” combined with the Boolean operator AND, covering the period from 2013 to 2024. Initially, 11 articles were retrieved, of which 9 met the inclusion criteria: pediatric population, focus on chronic nasal obstruction, and relationship with sleep and developmental outcomes. The selection process followed the PRISMA model. The results showed that adenoid hypertrophy is the main cause of chronic nasal obstruction in children and is associated with sleep-disordered breathing, cognitive impairments, behavioral alterations, school difficulties, and craniofacial deformities. Adenotonsillectomy proved effective in most cases; however, altered respiratory patterns may persist postoperatively. This integrative review highlights chronic nasal obstruction as a relevant risk factor for impaired child development. Early diagnosis and interdisciplinary management are essential to prevent or minimize its long-term effects. The evidence reinforces the need for further studies with standardized screening protocols and longitudinal follow-up.